Sun Protection Factor, Antioxidant, and in Silico Study of Some Synthesized Benzylidene Analogues of Ketamine Against Elastase and Collagenase - Eboh, Abraham; Owaba, Azibanasamesa; Frank-Oputu, Ayibaena; Igbereyivwe, Provider (Journal of Pure & Applied Sciences, 2025)
Background: The degradation of ozone layer is in part due to human activities, climate change. These have led to many skin diseases. Scientists are investigating for new alternative sun protection agents having low toxicity. Therefore, analogues of ketamine (benzylidenes) were investigated for sun protection ability. Objective: In this present research work, derivatives of ketamine synthesized from the department of Pharmaceutical and Medicinal Chemistry Niger Delta Uniersity Bayelsa state (D11-D15) were experimented for sun protection factor. Also, antioxidant and in vitro anti-elastase and anti-collagenase activities and in silico studies were carried out Methods: in vitro spectrophotometric determination of derivatives of ketamine were carried out, DPPH antiradical scavenging ability of D11-D15, total antioxidant capacity and ferric reducing antioxidant power were also evaluated on the compounds (D11-D15). Also in vitro spectrophotometric assays on anti-elastase and anti-collagenase were also carried out on (D11-D12) and lastly molecuar docking studies were carried out on (D11-D12) against the enzymes elastase and collagenase. Results: The results from the study revealed that D11-D15 at concentrations of 25, 50 and 100 µg/ml shows higher SPF values. Also, the total antioxidant capacity reported as microgram ascorbic acid equivalent/g compound shows that D14 > D11 > D13 > D12 > D15. Also, the DPPH radical scavenging potentials and ferric reducing antioxidant power reported as percentages and microgram gallic acid equivalent/g compound revealed higher values. The anti-elastase and anti-collagenase targeted with ketamine analogues showed that (D11-D15) inhibited elastase and collagenase activity results presented as IC50; these results were confirmed by the docking studies as the analogues bind more tightly to the active sites of elastase and collagenase better than sivelestat and acetylcysteine respectively. Conclusion: Our result shows that D11-D15 could serve as sun protection agents, antioxidants and antiaging especially in the cosmetic industry.